Conditional turning bands simulation in (2D, 3D) forecasting of various regionalized phenomena - Namysłowska-Wilczyńska, Barbara; Wilczyński, Artur (Symulacja warunkowa turning bands w prognozowaniu (2D, 3D) różnych zjawisk zregionalizowanych, 2011)
The paper presents the results of a conditional turning bands simulation and a research methodology based on nonlinear geostatistics, applied to the 2D and 3D forecasting of geological and mining parameters, environmental parameters and electrical demand. The turning bands method is used to simulate the stationary values of random functions Z(x), i.e. covariance function C. The input for the investigations were: geological and mining data from the sampling of mining headings in copper ore mines (relating to Cu grade in a recoverable deposit series) and results of chemical analyses of heavy metal (Cr) concentration in soils, representing environmental data and data on power demand in the nodes of 220 and 400 kV transmission networks. The intensity and extent of copper mineralization in the sedimentary rocks in Lubin-Sieroszowice area and those of soil pollution within the area directly affected by the industry in Upper Silesia as well as the distribution of average electrical loads for the whole territory of Poland were determined.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2011; Nr 196, s. 48-68
Keywords: geofizyka górnicza; górnictwo; prognozowanie; geostatystyka; geophysics; mining sector; forecasting; geostatistics